Synthesis and characterization of bulk single crystal hexagonal boron nitride from metal solvents - Clubine, Benjamin (Kansas State University, 2012)
Boron nitride is a purely synthetic material that has been known for over 150 years but only recently has sparked interest as a semiconductor material due to its potential in ultraviolet lasing and neutron detection. Thin-layer hexagonal boron nitride (hBN) is probably most attractive as a complementary material to graphene during its intense research endeavors. But for hBN to be successful in the realm of semiconductor technology, methods for growing large single crystals are critical, and its properties need to be accurately determined. In this study, hBN crystals were grown from metal solvents. The effects of soak temperature, soak time, source materials and their proportions on hBN crystal size and properties were investigated. The largest crystals of hBN measured five millimeters across and about 30 micrometers thick by precipitation from BN powder dissolved in a nickel-chromium solvent at 1700°C. High temperatures promoted outward growth of the crystal along the a-axis, whereas low temperatures promoted growth along the c-axis. Crystal growth at high temperatures also caused bulk hBN to adopt a triangular habit rather than a hexagonal one. A previously unreported method of synthesizing hBN was proven successful by substituting BN powder with elemental boron and a nitrogen ambient. XRD and Raman spectroscopy confirmed hBN from solution growth to be highly crystalline, with an 8.0 cm[superscript]-1 FWHM of the Raman peak being the narrowest reported. Photoluminescence spectra exhibited peaks mid-gap and near the band edge, suggesting impurities and defects in the hBN samples. However, high-purity reactants and post-growth annealing showed promise for synthesizing semiconductor-grade hBN. Several etchants were explored for defect-selective etching of hBN. A molten eutectic mixture of KOH/NaOH was the most effective defect-selective etchant of hBN at temperatures of 430-450°C for about one minute. The two prevalent hexagonal etch pit morphologies observed were deep, pointed-bottom pits and shallow, flat-bottom pits. TEM and SAED confirmed basal plane twists and dislocations in hBN crystals, but due to the highly anisotropic nature of hBN, their existence may be inevitable no matter the growth technique.
Keywords: hexagonal boron nitride; bulk crystal growth; Chemical Engineering (0542); Materials Science (0794)